Optical encryption and QR codes: Secure and noise-free information retrieval - Barrera, John Fredy (2013)
We introduce for the first time the concept of an information “container” before a standard optical encrypting procedure. The “container” selected is a QR code which offers the main advantage of being tolerant to pollutant speckle noise. Besides, the QR code can be read by smartphones, a massively used device. Additionally, QR code includes another secure step to the encrypting benefits the optical methods provide. The QR is generated by means of worldwide free available software. The concept development probes that speckle noise polluting the outcomes of normal optical encrypting procedures can be avoided, then making more attractive the adoption of these techniques. Actual smartphone collected results are shown to validate our proposal.